Assouad dimensions and spectra of Moran cut-out sets. (February 2019) - Chen, Haipeng
Abstract: Given a suitable gap sequence and some assumptions, we discuss the Assouad dimensions and spectra of Moran cut-out sets by the equivalent but more accessible definitions of Assouad dimensions and spectra. As an application, we discuss the Assouad dimensions and spectra between Moran cut-out sets and Moran sets.